FREQUENCY MODIFIED APPROACH FOR FATIGUE LIFE PREDICTION OF PMMA - HUANG AiFeng; YAO WeiXing; CHEN Fang (Jixie qiangdu)
The fatigue tests of Plexiglas Resist45 PMMA at different frequencies were carried out and the S-N curves together with hysteresis loops were obtained. The results show that the fatigue life increases with frequency at low frequency domain. Creep damage and mechanical property rate-dependence are two attributes of frequency effect on fatigue life. And the frequency modified approach was employed to describe and estimate the fatigue life under different frequencies at low frequency domain and the calculated results are consistent with the experimental results.